Climate Change and Type 2 Diabetes in Senegal, a Sub-Saharan Country: Interconnected Threats to Health and Development - Haque, Azizul; Pant, Anudeep B. (British Journal of Healthcare and Medical Research, 2025)
Type 2 Diabetes Mellitus (T2DM), a disease once thought to be rare and only affecting the wealthy, is now on the rise across Senegal, a sub-Saharan African country. Genetics play a role in insulin production, a key factor in type 2 diabetes, however, the disease is also heavily influenced by environmental factors. There is limited data available regarding diabetes in sub-Saharan countries, which highlights the importance of discussing the underlying reasons for rapid progression of the disease in the region. Here, we provide a broad view of the influence of climate change on the multifactorial drivers of type 2 diabetes across the population in Senegal, and to discuss the potential mechanisms behind the intersecting effects between them. This review highlights evidenced-based information to shed light on the potential linkage between T2DM and environmental factors like climate change, pollution, urbanization and lifestyle choices (such as the consumption of ultra-processed foods, limited physical activities). We propose that these modifiable risk factors are promoting diabetes in Senegal and other sub-Saharan countries. We discuss the impact (mechanistic) of air pollution and diet on the gut microbiome and the resulting chronic inflammation that could propel the development of T2DM. Finally, this paper recommends various public health policies, to curb the progression of diabetes, which is is still in the initial stages in Senegal. Taken together, this paper outlines opportunities to design new and effective targeted prevention strategies, which can be applied to mitigate the rapid increase of diabetes in Senegal and beyond.